Stability, interparticle interactions and catalytic performance of gold nanoparticles synthesized through ionic liquid mediated oil palm leaves extract. Issue 4 (August 2018) - Irfan, Muhammad; Moniruzzaman, Muhammad; Ahmad, Tausif; Osman, Ola Yahia; Mandal, Pradip Chandra; Bhattacharjee, Sekhar; Hussain, Murid
Graphical abstract: Highlights: Synthesis of AuNPs using ionic liquid mediated oil palm leaves extract. Volume of extract has strong influence on reduction rate and particles size. Multiple qualitative approaches used to predict the colloidal stability of AuNPs. Quantitative method established to understand the stability ratio of AuNPs. Changes in catalytic performance of synthesized AuNPs over time were assessed. Abstract: The particles size is an influential factor to control the optical, physicochemical, and electronic properties of gold nanoparticles (AuNPs). Any variation in the particles size can change these properties that not only confine the scope of AuNPs but also diminish the colloidal stability of solution. In this work, AuNPs are synthesized using ionic liquid mediated oil palm leaves (OPL) extract and their colloidal stability, interparticle interactions and catalytic performances as a function of time are investigated. Various analytical techniques such as GC–MS, UV–vis spectrophotometer, DLS and FESEM analyses were utilized to explain the different phases involved in bio- synthesis of AuNPs. In addition, synthesized AuNPs of different ages were used for catalytic degradation of methylene blue (MB) to examine their catalytic performance as a function of time. Moreover, the qualitative techniques including reduction of absorbance, variation in surface plasmon resonance (SPR) peaks, change of particles size and zeta potential were used to endorse the colloidal stability of AuNPs. Furthermore, an analytical method was established by considering particles' interaction as described by Derjaugin-Landau-Verwey-Overbeek's theory to establish a quantitative definition of stability. Finally, the values of hydrodynamic particles size and zeta potential were fitted to estimate stability ratio of AuNP which provided precise indication of the colloidal stability. The respective reaction rate constants of AuNPs for degradation of MB were found to be 0.272 and 0.258 min −1 after day 1 and day 60 respectively, indicating an efficient activity of these particles for an extended period of reaction time.